Implementation of Assistive Technology for Visually Impaired Students in the Formal Education Sector - Misbahul Arifin; Yusuf, Munawir; Sunardi, Sunardi; Rahman, Abdul (Angstrom Centre of Education, 2024)
The recent shift in technology usage has impacted education significantly, including institutions that provide services for students with visual impairments. This article aims to analyze the role of assistive technology in the learning of students with visual impairments. This article uses the research method of article review with meta-analysis. The source of the review of this article is articles sourced from reputable articles on Google and Scopus by considering the same themes and keywords in this study, so that the discussion becomes more coherent and relevant. Based on the results of the literature study, it is found that the use of assistive technology in inclusive education focuses on the use of technology to practice, and to assist in the learning process. Assistive technology also provides accessibility to learners in various ways to complete their tasks more easily and independently that they could not previously complete.